2014
DOI: 10.5539/esr.v4n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Basin Framework and Basement Structuring of Lower Benue Trough, West Africa based on Regional Magnetic Field Data: Tectonic and Hydrocarbon Implications

Abstract: Results from magnetic field modelling of the Lower Benue Trough, West Africa revealed thick sedimentation with maximum values in the neigbourhood of 7,000m-10,000m. This is in contrast to the average value of 5000m suggested by earlier studies. The thick sedimentation represent thermal sag which is a regional post-rift subsidence associated with West and Central Africa rift systems. N-S, NNW-SSE and E-W structural fabrics interpreted from the transformed magnetic data bound the trough. The subsurface magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The formation of the southern Nigeria sedimentary basin followed the break-up of the South American and African continents in the Early Cretaceous (Murat 1972). Several authors have used structural, stratigraphic, geomorphologic and palaeonotologic evidence to support a rift model of the basin (Reyment 1969;Petters 1978;Benkhlil 1989;Oyedim et al 2009;Igwesi and Umego 2013;Okiwelu et al 2015). The development of the Benue Trough provided the main structural control and framework for the subsequent geologic evolution of the region.…”
Section: Geology Of the Areamentioning
confidence: 99%
“…The formation of the southern Nigeria sedimentary basin followed the break-up of the South American and African continents in the Early Cretaceous (Murat 1972). Several authors have used structural, stratigraphic, geomorphologic and palaeonotologic evidence to support a rift model of the basin (Reyment 1969;Petters 1978;Benkhlil 1989;Oyedim et al 2009;Igwesi and Umego 2013;Okiwelu et al 2015). The development of the Benue Trough provided the main structural control and framework for the subsequent geologic evolution of the region.…”
Section: Geology Of the Areamentioning
confidence: 99%
“…Also [32] reported that in the Gongola basin a series of N-S trending faults appear to dominate the region, subdividing it in to parallel to sub parallel N-S and fault bound basins. Also [33] who worked on the Lower Bebue Trough ( Mamfe Embayment and environs) recognized grabens ,half grabens and deep sedimentation (depocentres) and interpreted them as hydrocarbon related structures. By implication recognition and mapping of the horsts-grabens in the Benue Rift is crucial in any hydrocarbon prospecting venture.…”
Section: Hydrocarbon Prospect Of Nigeria's Gongola Basin Based On Gramentioning
confidence: 99%
“…It has been described as the failed arm of a radial rift system which spans from the northern parts of the Niger Delta to the fringes of the Chad Basin [5,4,6]. The length of the Trough is about 700 km and it bifurcates at the northeastern end with its width ranging from 100 km to 150 km [3,7] Thick sedimentation accompanied by basement faulting, rifting, subsistence and opening of the South Atlantic Ocean gave rise to cycles of transgression and regression producing thicknesses ranging from 7000 -10000 meters [3,7]. The Trough has been distinctly divided by authors into the Lower, Middle and Upper [4,8,7,6].…”
Section: Introductionmentioning
confidence: 99%
“…The length of the Trough is about 700 km and it bifurcates at the northeastern end with its width ranging from 100 km to 150 km [3,7] Thick sedimentation accompanied by basement faulting, rifting, subsistence and opening of the South Atlantic Ocean gave rise to cycles of transgression and regression producing thicknesses ranging from 7000 -10000 meters [3,7]. The Trough has been distinctly divided by authors into the Lower, Middle and Upper [4,8,7,6]. Outstanding deformational structures as a result of tectonism in the Trough include: Abakiliki Anticline, Anambra and Afikpo Synclines (Lower Benue), Keana Anticline, Awe Syncline (Middle Benue), Zambuk Ridge (Upper Benue) [3,4,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation